STRATEGI PENGELOLAAN KEUANGAN YANG DISESUAIKAN DENGAN ERA MODERN PADA PELAKU UMKM DI ORKI TANGSEL - Rizka Wahyuni Amelia; Lina Nofiana; Hasanudin (Abdi Jurnal Publikasi, 2025)
Financial management is a fundamental aspect in maintaining the sustainability of MSMEs, especially amidst the demands of the modern digital era. This community service activity aims to improve the ability of MSME actors in ORKI Tangerang Selatan to manage finances effectively and adaptively to technological developments. The activity was carried out in the form of a two-day training that included basic financial education, cash flow recording simulations, and training in the use of simple financial applications. The results of the pre-test and post-test showed a significant increase in participant understanding. Most participants stated that they were ready to implement a digital financial recording system. This activity shows that an applicable and contextual education strategy is very effective in encouraging MSME actors towards professionalism and business sustainability in the digital era.